Parent-Child Interaction in the First Year Of Life - Rosenbaum, Peter (1975)
The first year of life traditionally refers to the growth and development of an infant. Recent studies have disclosed the powerful effects exerted by young babies upon their parents. These influences depend upon distinct, measurable personality and temperamental factors present in the infant from birth. Parent/child attachment has been observed, in both normal nurseries and premature intensive-care units, and appears to comprise a series of species-specific behaviors. Inadequate or incomplete bonding has been strongly correlated with subsequent ‘disorders of parenting’, including non-organic ‘failure to thrive’ and the abused child syndrome. The implications of these current discoveries for family physicians are discussed.